The role of protein in the growth and development of muscle mass in strength athletes - Nikitchenko, S.Yu.; Fedyaev, N.A.; Musaev, I.S.H.; Grigoreva, A.Yu. (Theory and Practice of Physical Culture, 2025)
Abstract Objective of the study is to systematise and analyse current scientific data on the role of protein in skeletal muscle adaptations during regular strength training. Methods and structure of the study. A comparative analysis was conducted of a group of arm wrestlers (n=20, males aged 18-25 years, with at least 2 years of training experience), who were divided into two subgroups depending on their daily protein intake: control group (up to 1.4 g/kg of body weight) and experimental group (2.0-2.2 g/kg of body weight). Over a period of 10 weeks, changes in muscle mass (using bioimpedance analysis) and increases in competitive strength (based on the results of specific dynamometric tests on the wrist and elbow flexor) were monitored. Results and conclusions. The experimental group showed an average increase in lean muscle mass of 1.4 kg compared to 0.6 kg in the control group, as well as an increase in competitive strength of 13.2% compared to 6.7%, respectively. The study also analyses the effect of protein intake timing (before, after and during training), it’s even distribution throughout the day and the use of protein supplements in the athletes' diet. The risks of excessive protein consumption, including the potential strain on the kidneys and digestive system, and the importance of an individual approach to an athlete's diet are discussed separately. The article is intended for specialists in the field of sports medicine, nutritionists and coaches working with strength athletes.